Research on Employee Performance through Transactional Leadership and Organizational Commitment: A Case in FPT University Danang - Tan, Trinh Le; Quan, Nguyen Quoc; Tung, Tran Minh (American Journal of Social Sciences and Humanities, 2021)
The quality of training in FPT University Danang (FUDN) is considered as most important criteria in strategic development. In order to advanced quality of training FUDN always focus on human resource quality. In order to increase employee performance, there are many solutions for it, therefore we need to discover factors affecting for specific case. This research have tested relationship between transactional leadership, organizational commitment and employee performance. Authors using previous studies for collecting secondary data and recommendation proposed research model, Through all items of each measurement, authors design questionnaire and survey 55 instructor and staff in FUDN. We use quantitative research for testing hypostheses in proposed research model. Data was analyzed by SPSS 20 through statistic technique. Research have shown that Transactional leadership and Organizational commitment affect to employee performance. FUDN board need to create effective policy as well as changing leadership style to increase commitment from employee and attract high talent instructor.